Chromatographic evaluation of curcumin content in commercial samples - Sophia Messa; Marili Villa Nova Rodrigues; Carla Lea de Camargo Vianna; Rodney Alexandre Ferreira Rodrigues (Brazilian Journal of Food Technology, 2025)
Abstract Turmeric, also known as ground saffron, is a widely used spice that colours and flavours traditional dishes. It has antioxidant, antimicrobial, and coloring properties due to the presence of curcumin in its composition. Studies indicate that its daily consumption promotes a reduction in the symptoms of chronic non-communicable diseases such as obesity, diabetes, cancer, Alzheimer's, and Parkinson's, among others, and can be used in therapies for longevity. Thus, this study aimed to quantify the curcumin present in commercial turmeric samples using the High-Performance Liquid Chromatography method. Curcumin extraction was performed using the Soxhlet system, with the samples previously defatted with hexane. The samples of turmeric powder showed a wide variation in curcumin content (0.06% to 2.06% w/w), highlighting the need for stricter quality control, not compromising its application as a food input and its bioactivity.